Aldosterone activates ERK phosphorylation in the nucleus tractus solitarius. (23rd April 2023) - Wang, Rui; Fang, Dan; Lin, Tingting; Liang, Wenhui; Qiao, Hu
Highlights: ALD can lead to ERK1/2 phosphorylation quickly in the NTS. G1 (GPER agonist) can lead to ERK1/2 phosphorylation quickly in the NTS. G15 (GPER antagonist) can partially block the increasing effect on ERK1/2 phosphorylation caused by ALD / G1. Abstract: Sodium intake effect of aldosterone has attracted much attention. In our recent study, aldosterone can play a nongenomic regulatory role on rapid sodium intake in the NTS (nucleus tractus solitarius) by activating G protein-coupled estrogen receptor (GPER), and it exhibited an obvious time-dependent and concentration-dependent regulation. However, the molecular mechanism how aldosterone regulated sodium intake rapidly, is unclear. To determine the molecular mechanism of rapid sodium intake regulation of aldosterone, rats with a stainless-steel cannula in the NTS were used (n = 6 each subgroup), and were injected different concentrations of aldosterone/G1 (GPER agonist)/G15 (GPER antagonist) at different time points, then detected ERK1/2 protein expression. The results showed that aldosterone/G1 increased the ERK1/2 protein phosphorylation, and presented a time-dependent and concentration-dependent similar to sodium intake; Meanwhile, G15 partially blocked this effect at least. Taken together, we postulate that ERK1/2 protein may influence nongenomic sodium intake regulated by aldosterone at nucleus tractus solitarius level.